Escolas de educação profissional no Ceará : um estudo avaliativo acerca dos fatores que contribuem para (in)eficácia dos resultados do SPAECE - Silva, Lucas Melgaço da (2020)
Identifying and publicizing the effectiveness of didactic-pedagogical policies and strategies are necessary to improve Basic Education, as well as to observe the positive/negative results of external evaluations and the consistency with which educational activities are developed within schools. This work aimed to evaluate the factors (actions and strategies) that contribute to the (in)effectiveness of external evaluation results by the Permanent Evaluation System of Basic Education in Ceará State (SPAECE), through a comparative study of the Professional Education State Schools of Ceará (EEEP's). Specifically, we sought to further studies about professional education and its relationship with high school, reflected in educational evaluation and its relationship with education quality; actions and strategies developed by the Professional Education State Schools of Ceará (EEEP) were compared, with higher and lower results from the evaluations of the Permanent Evaluation System of Basic Education of Ceará (SPAECE) and their reflections on the results obtained from this evaluation; the educational potential and deficiencies of the Professional Education State Schools of Ceará (EEEP) were identified; and adjustments to didactic-pedagogical, management and structural practices were proposed to improve results in external evaluations and student learning. These schools emerged through a partnership between the Federal and State Government, with an action program to strengthen education integrated with professional education in state networks. In recent years, the Department of Education of Ceará has increasingly valued and invested in the educational offer, making it necessary to highlight the importance of evaluating the results of these institutions. Considering this, qualitative and descriptive methods were used in a comparative study carried out through in loco observations, official documents, and websites, and by applying questionnaires and semi-structured interviews. These were based on authors who discuss topics such as: professional education, high school, educational evaluation, management, teacher training, quality in education, among others. The results confirm the need for alignment in the education system of the Professional Education State Schools of Ceará, considering the redefinition and implementation of ten factors, namely: physical structure, pedagogical political project, professional curriculum, management, motivation, discipline, programs and projects, teacher training, pedagogical work and evaluation. The results refute the strong relationship between the institution’s physical structure and educational quality. Finally, an improvement scenario is proposed for institutions that have any difficulties establishing themselves among schools of excellence, and elements to elaborate educational policies are provided.